Advancing digital pedagogy in culinary education: The ADIT framework - Aditia Gustiana Gunawan; Rina Rifqie Mariana; P. Purnomo; Eddy Sutadji; Quinnera Putra Joshua (Universitas Muhammadiyah Malang, 2026)
Background-The implementation of VR in culinary education remains limited due to the lack of a systematic learning model that integrates adaptive learning, immersive environments, and technological pedagogy. Objectives-This study aims to develop a learning model that aligns technological innovations in vocational learning. Method-This study used the PRISMA methodology to review literature published between 2017 and 2025 across major academic databases. From an initial pool of studies, 39 peer-reviewed articles met the inclusion criteria and were analyzed to identify dominant theories, commonly used instructional frameworks, and key design components in VR-based vocational education. Results-The findings indicate that widely adopted models such as ADDIE, ASSURE, Dick and Carey, TPACK, and the Technology Integration Matrix lack integrated mechanisms to address adaptive feedback, multisensory engagement, and real-time performance analytics. This limitation in culinary education is that skill acquisition relies on the synchronization of cognitive processes, sensory perception (e.g., visual presentation, timing, and procedural accuracy), and iterative feedback. Conclusions- The ADIT model, consisting of three core components: Adaptive Assessment, Immersive Instructional Design, and Technology Integration, is capable of incorporating real-time analytics to monitor learner performance, enabling dynamic feedback loops and personalized learning paths that connect pedagogy, technology, and professional training.